C02 CAPTURE USING SOLID SUPPORTED IONIC LIQUID [HMIM][TF2N] - MAT DAGANG, NURUL SAFIAH (2016)
Ionic liquids (ILs) are getting more attention in the research world due to its green properties such as thermallyand chemically stable, non-volatile, and can be tuned or designed fora particular application. ILs havebeenprovento givepromising results in CO2 capture applications. However, the viscosity of ILs is high which can limit the masstransferof molecules in the ILs. Theuse of water to reduce the viscosity however leads to ILs loss due to evaporation and corrosion problem. Impregnation of ILs into porous solid support may be an alternative to overcome this problem. The preliminary stllHv invnWgH the* iirmiym-iQtinn nf 1 fWfO/, ftimiml fTf-MI intn gif>,. nr*A A1~r~>. At 1 in ~ ~"—J —"~ " ~~ ' —— ..^» ^u^.w^.wi.ivn vj. J-uT.v/u l^iiliiiilij |^ i lillj liiCO kJlV/Z U1LU i 11/Oj. ill i"JU bar and 25 °C, Si02 with [hmim][Tf2N] (denoted as 10wt%[hmim][Tf2N]-Si) showed the highest adsorption compared to 10wt%[hmim][Tf2N]-Al, [hmim][Tf2N], Si02 and AI2O3. Further investigation onSi02 as solid supportwasperformedto study the effect of weight percentage of [hmim][Tf2N], temperature (25-60 °C), and pressure(2-30 bar) on the CO2 adsorption capacity.